Ectopic Expression of PAP1 Leads to Anthocyanin Accumulation and Novel Floral Color in Genetically Engineered Goldenrod (Solidago canadensis L.) - Skaliter, Oded; Ravid, Jasmin; Shklarman, Elena; Ketrarou, Nadav; Shpayer, Noam; Ben Ari, Julius; Dvir, Gony; Farhi, Moran; Yue, Yuling; Vainstein, Alexander (Frontiers in Plant Science, 2019)
Floral pigmentation is of major importance to the ornamental industry, which is constantly searching for cultivars with novel colors. Goldenrod (Solidago canadensis) has monochromatic yellow carotenoid-containing flowers that cannot be modified using classical breeding approaches due to a limited gene pool. To generate Solidago with novel colors through metabolic engineering, we first developed a procedure for its regeneration and transformation. Applicability of different cytokinins for adventitious regeneration was examined in the commercial cv. Tara, with zeatin yielding higher efficiency than 6-benzylaminopurine or thidiazuron. A comparison of regeneration of commercial cvs. Tara, Golden Glory and Ivory Glory revealed Tara to be the most potent, with an efficiency of 86% (number of shoots per 100 leaf explants). Agrobacterium-based transformation efficiency was highest for cv. Golden Glory (5 independent transgenic shoots per 100 explants) based on kanamycin selection and the GUS reporter gene. In an attempt to promote anthocyanin biosynthesis, we generated transgenic Solidago expressing snapdragon (Antirrhinum majus) Rosea1 and Delila, as well as Arabidopsis thaliana PRODUCTION OF ANTHOCYANIN PIGMENT 1 (PAP1) transcription factors. Transgenic cv. Golden Glory expressing cauliflower mosaic virus 35S-driven PAP1 generated red flowers that accumulated delphinidin and its methylated derivatives, as compared to control yellow flowers in the GUS-expressing plants. The protocol described here allows efficient engineering of Solidago for novel coloration and improved agricultural traits.